2018
DOI: 10.12973/iji.2018.11457a
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of Theses and Articles on Ethical Leadership

Abstract: In this study, it was aimed to examine the postgraduate theses and articles on ethical leadership in Turkey by gathering them through the document analysis method and by using content analysis. In this direction, all of the postgraduate theses and articles that can be accessed in the electronic environment as a full-text were included in the scope of the study. As a result of the research, it was determined that 96 postgraduate theses and 33 articles were conducted in Turkey from 2006-2018 (April) on ethical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
3
0
4
Order By: Relevance
“…Türkiye'de yapılan ve eğitim dilinin çoğunluğu Türkçe olan ve yükseköğretim kurumlarında yapılan çalışmaların çoğunluğunun Türkçe olması, beklenen bir sonuçtur. Lisansüstü tezlerin incelendiği araştırmalarda da benzer sonuçlara ulaşmak mümkündür (Aydın, 2018, Kıranlı Güngör, 2018Aydın, Selvitopu ve Kaya, 2018). Doktora tezleri, danışmanları açısından incelendiğinde %70'inin profesör doktor tarafından %21'inin doçent doktor tarafından yönetildiği, %14'ünün yardımcı doçent tarafından yönetildiği saptanmıştır.…”
Section: Tartışma Ve Sonuçunclassified
See 3 more Smart Citations
“…Türkiye'de yapılan ve eğitim dilinin çoğunluğu Türkçe olan ve yükseköğretim kurumlarında yapılan çalışmaların çoğunluğunun Türkçe olması, beklenen bir sonuçtur. Lisansüstü tezlerin incelendiği araştırmalarda da benzer sonuçlara ulaşmak mümkündür (Aydın, 2018, Kıranlı Güngör, 2018Aydın, Selvitopu ve Kaya, 2018). Doktora tezleri, danışmanları açısından incelendiğinde %70'inin profesör doktor tarafından %21'inin doçent doktor tarafından yönetildiği, %14'ünün yardımcı doçent tarafından yönetildiği saptanmıştır.…”
Section: Tartışma Ve Sonuçunclassified
“…İncelenen doktora tezlerinin %51'i nicel yöntemler, %28'i nitel yöntemler ve %29'u karma araştırma yöntemleri ile göre hazırlanmıştır. Tez ve makaleleri inceleyen diğer çalışmalarda nicel yöntemin ağırlıklı çalışıldığı, nitel ve karma araştırma yöntemlerine ise bu araştırmya göre çok az sayıda yer verildiği görülmektedir (Akyol ve Akçay, 2015;Akyol ve Yavuzkurt, 2016;Kütükçü, 2017;Aydın, 2018;Kıranlı Güngör, 2018;Aydın, Selvitopu ve Kaya, 2018) Bu araştırma, bu yönüyle literatürdeki diğer çalışmalardan ayrışmaktadır. Doktora tezlerine veri toplama araçları açısından bakıldığında; en fazla tercih edilen veri toplam aracının anket/ölçek olduğu, ardından dokümanların geldiği görülmektedir.…”
Section: Tartışma Ve Sonuçunclassified
See 2 more Smart Citations
“…Based on the analysis and synthesis results of literature on instructional leadership involving seven lecturers who are experts in the area of educational administration, they have validated the contents regarding their opinion towards instructional leadership development (Güngör, 2018). The results showed that the information that provided insights from the possible effects of synthesizing became the items to measure the roles of instructional leadership…”
Section: Instructional Leadership Constructsmentioning
confidence: 99%